Pendidikan Agama bagi Anak : Antara Karakteristik dan Treatment - Djami'atul Islamiyah (Prodi PGMI IAIN Salatiga, 2009)
Religious education is not absolutely difficult in terms of its materials. The objective of the education is, however, complicated because it aims at perfecting children in terms of cognitive as well as affective aspects. The very beginning comprehension of the children to the concept of God as well as their psychological characteristics of their religiosity will be helpful to the choice of actions in the context of religious education for the children. Religion hold a significant role to educate children, as a start point to provide the fundamental aspect of every part of future live.